The Challenges of Long Term Ecological Research: A Historical Analysis - Waide, Robert B.; Kingsland, Sharon E. (Archimedes, New Studies in the History and Philosophy of Science and Technology, 2021)
XIX, 478 p. 56 illus., 4 illus. in color.